The student-teacher relationship scale in a Greek sample of preadolescents: reliability and validity data - P. Galanaki, Evangelia; D. Vassilopoulou, Helen (Psychology: the Journal of the Hellenic Psychological Society, 2020)
THE ABSTRACT IS AVAILABLE IN THE PDF